RESEARCH ON PEDAGOGICAL APPROACHES IN TEACHING ORGANIC CHEMISTRY - Mammadova Aynur Teyyub; Jafarli Gunel Hafiz (Progress in Science, 2025)
The article examines modern pedagogical approaches applied in the teaching of organic chemistry. Due to the complex content structure, abstract concepts and the requirement of high-level chemical thinking from students, traditional teaching methods are often insufficient. In this context, the effectiveness of methods such as problem-based learning, project-based learning, constructive approach, laboratory-based learning, and the application of digital and interactive technologies is analyzed.